2020
DOI: 10.1002/admi.202001146
|View full text |Cite
|
Sign up to set email alerts
|

Forming‐Free, Nonvolatile, and Flexible Resistive Random‐Access Memory Using Bismuth Iodide/van der Waals Materials Heterostructures

Abstract: next-generation memory devices such as ferroelectric random-access memory, magnetoresistive random-access memory, and resistive random-access memory (RRAM) have been intensively researched and developed. [4-12] Of these innovative nonvolatile memories, RRAM offers low power consumption, fast response speed, long retention time, high scalability, multistate data-storage capability, and a simple metalinsulator-metal structure. [9,13,14] Information storage in the RRAM is achieved by altering the resistance of it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…In a different approach, Li et al have demonstrated a flexible bismuth iodide (BiI 3 ) memristor using thermal evaporation and CVD techniques (Figure a–c) . The devices, having graphene/copper foil as the electrode, demonstrated a forming-free property and have an ON/OFF ratio of 10 4 with set and reset voltages of 0.3 V and −0.15 V, respectively.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In a different approach, Li et al have demonstrated a flexible bismuth iodide (BiI 3 ) memristor using thermal evaporation and CVD techniques (Figure a–c) . The devices, having graphene/copper foil as the electrode, demonstrated a forming-free property and have an ON/OFF ratio of 10 4 with set and reset voltages of 0.3 V and −0.15 V, respectively.…”
mentioning
confidence: 99%
“…(a–c) Lead-free flexible memristors: (a) a photograph of the copper foil/graphene/BiI 3 /Au devices, (b) I – V plots and, (c) resistance of the of the BiI 3 memristors as a function of the bending cycle at a bending radius of 8.75 mm. Reprinted with permission from ref . Copyright 2020 John Wiley and Sons.…”
mentioning
confidence: 99%
“…It demonstrates that there exist metallic states of bismuth atoms at the interfaces between the bismuth iodide and the electrode without bias, which is in a good agreement with the previous literature. 49,50 Moreover, compared to the pristine Ag 3d spectra, the XPS peaks of Ag 3d are initially located at 368.2 and 374.2 eV, as shown in Figure S3, corresponding to 3d 7/2 and 3d 5/2 of metallic Ag. 63 With BiI 3 deposition on the Ag substrate, both peaks are gradually shifted to 367.4 and 374.4 eV, corresponding to the signal of AgI.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…[23] There are reports which potentially demonstrate the WORM properties together with resistive switching in oxide-based materials. [24,25] The bismuth-rich materials, such as BiFeO 3 , BiI 3 , and Bi 4 Ti 3 O 2 [26][27][28] are getting attention for showing memory characteristics. Among these, sillenite Bi 12 MO 20 (M = Fe, Ti, Zn, Ge, etc.)…”
Section: Doi: 101002/pssa202200744mentioning
confidence: 99%